Optically driven microtools with an antibody‐immobilised surface for on‐site cell assembly - Shuntaro Mori; Takumi Ito; Hidekuni Takao; Fusao Shimokawa; Kyohei Terao (IET Nanobiotechnology)
Abstract To enable the accurate reproduction of organs in vitro, and improve drug screening efficiency and regenerative medicine research, it is necessary to assemble cells with single‐cell resolution to form cell clusters. However, a method to assemble such forms has not been developed. In this study, a platform for on‐site cell assembly at the single‐cell level using optically driven microtools in a microfluidic device is developed. The microtool was fabricated by SU‐8 photolithography, and antibodies were immobilised on its surface. The cells were captured by the microtool through the bindings between the antibodies on the microtool and the antigens on the cell membrane. Transmembrane proteins, CD51/61 and CD44 that facilitate cell adhesion, commonly found on the surface of cancer cells were targeted. The microtool containing antibodies for CD51/61 and CD44 proteins was manipulated using optical tweezers to capture HeLa cells placed on a microfluidic device. A comparison of the adhesion rates of different surface treatments showed the superiority of the antibody‐immobilised microtool. The assembly of multiple cells into a cluster by repeating the cell capture process is further demonstrated. The geometry and surface function of the microtool can be modified according to the cell assembly requirements. The platform can be used in regenerative medicine and drug screening to produce cell clusters that closely resemble tissues and organs in vivo.